Co-existence of Multiple Anaplasma Species and Variants in Ticks Feeding on Hedgehogs or Cattle Poses Potential Threats of Anaplasmosis to Humans and Livestock in Eastern China - Qi, Yong; Ai, Lele; Zhu, Changqiang; Lu, Yongfeng; Lv, Ruichen; Mao, Yingqing; Lu, Nianhong; Tan, Weilong (Frontiers in Microbiology, 2022)
Background Anaplasma spp., causative agents of anaplasmosis, pose remarkable negative influences on public health and economic losses in livestock farming. Co-infections/co-existences of various Anaplasma spp. may facilitate pathogen interactions and emergence of novel variants, pose potential threats to public health and economic losses of livestock farming, and raise challenges of detection and diagnosis. Information regarding co-infection/co-existence of Anaplasma in their vector ticks and wild animals is limited and needs urgent investigations. Methods Wild hedgehogs and ticks from hedgehogs and cattle were collected from Jiangsu province, Eastern China, and DNA was extracted from hedgehog organs and tick homogenates. Various genus- or species-specific polymerase chain reaction (PCR) or nested PCR amplifications targeting 16S ribosomal RNA (rrs), msp4, or groEL gene coupled with sequencing were conducted to identify Anaplasma spp. Results Anaplasma phagocytophilum (0.6%, 1/168), A. marginale (1.2%, 2/168), A. platys variants xyn10pt-1 (7.7%, 13/168), xyn21pt-2 (1.8%, 3/168), and xyn3pt-3 (1.8%, 3/168), A. bovis variant cwp72bo-1 (7.1%, 12/168), and a novel Candidatus Cryptoplasma sp. (0.6%, 1/168) were identified in Haemaphysalis longicornis ticks from cattle, A. platys variant xyn10pt-1 (11.4%, 20/173), and A. bovis variants cwp72bo-1 (6.9%, 12/173) and cwp55-36bo-2 (0.6%, 1/173) were detected in H. flava ticks from hedgehogs, and only A. bovis variant cwp72bo-1 (46.7%, 15/32) was identified in Erinaceus amurensis hedgehogs. Various co-existence combinations were found only in ticks. Conclusion Co-existences of various Anaplasma spp. and variants in H. flava and H. longicornis were detected for the first time in the world. The high infection rate of A. bovis in hedgehogs and its moderate infection rate in their parasitic ticks suggested that Er. amurensis hedgehog could be an important reservoir of A. bovis, rather than A. platys. Horizontal transmission of Anaplasma spp. may exist among different tick species via their shared hosts in the investigated area. This study provided epidemiological data that could be crucial for the strategy development in early warning, prevention and control of the potential Anaplasma infection.